Sinergi Kampus dan Sekolah dalam Meningkatkan Literasi Pengasuhan: Studi Kasus Seminar Parenting oleh KKM UIN Maulana Malik Ibrahim Malang - Qorin, Najwa Aliva; Ismail, Zakia Maryam Raihana (Maliki Interdisciplinary Journal, 2025)
The parenting seminar held at MI Bustanul Ulum in Batu City was a form of community service aimed at enhancing parental understanding of the importance of parenting styles in fostering children’s independence. Through material presentation and interactive discussions, participants were introduced to the concept of spoiled children, its causes, and the long-term effects of permissive and authoritarian parenting. The seminar was facilitated by a lecturer from the Early Childhood Islamic Education program at UIN Malang. The outcomes indicate that parents should distinguish between children’s needs and wants, apply consistent boundaries, and assign age-appropriate responsibilities. With the right approach and collaboration between family and school, the development of responsible and independent children can be achieved. This seminar also served as a reflective space for parents to evaluate their parenting practices.